Control of Buck Converter Using Artificial Neural Network - Rahyu Rahmadani, Ranti; Dewi, Citra (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Electrical energy has an important role in various aspects of life. Electrical energy is used in the form of alternating current (AC) voltage and direct current (DC) voltage. To produce a direct voltage (DC) that varies and as needed, a power converter is needed that is equipped with a control system so that the resulting voltage remains stable and does not experience overvoltage or undervoltage. In this research, the converter used is a buck converter. Because the buck converter is a nonlinear system, it requires a control system with a dynamic response rate. So it is necessary to design a buck converter by applying a control system that can maintain the stability of the buck converter output voltage efficiently and adaptively such as the Artificial Neural Network (ANN) method. The control proposed system will be implemented using an Arduino ATMega2560 programmed through Simulink Matlab. To test the effectiveness of this control system, several experiments will be conducted with an input voltage of 24 Volts and outputs worth 9 and 12 Volts. From this test, a voltage error of 0.1 Volt was obtained in the experiment with constant voltage and constant load criteria, proving that the control has successfully controlled the buck converter output voltage according to the reference voltage